RNA Sequencing Identifies Novel Signaling Pathways and Potential Drug Target Genes Induced by FOSL1 in Glioma Progression and Stemness - Guo S; Sidhu R; Ramar V; Guo AA; Wang G; Liu M (Biologics: Targets & Therapy)
Shanchun Guo,1 Rajveer Sidhu,2 Vanajothi Ramar,2 Alyssa A Guo,3 Guangdi Wang,1 Mingli Liu2 1RCMI Cancer Research Center and Department of Chemistry, Xavier University, New Orleans, LA, USA; 2Department of Microbiology, Biochemistry & Immunology, Morehouse School of Medicine, Atlanta, GA, USA; 3Wake Forest University School of Medicine, Winston-Salem, NC, USACorrespondence: Mingli Liu, Email mliu@msm.eduBackground: Glioblastoma is a highly aggressive brain tumor, and the transition from the proneural to mesenchymal subtype is associated with more aggressive and therapy-resistant features. However, the signaling pathways and genes involved in this transition remain largely undefined.Methods: We utilized patient-derived xenograft (PDX) samples of glioblastoma, specifically PDX-L14, which exhibit both negative and overexpressed FOSL1 expression. mRNA expression profiles were assessed by RNA sequencing in these samples, followed by gene ontology (GO) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, and Gene Set Enrichment Analysis (GSEA). Validation of the hub genes was performed using qPCR and immunohistochemistry assays.Results: Differentially expressed genes (DEGs) between FOSL1 overexpression groups were predominantly involved in ferroptosis, immune response, angiogenesis, vascular mimicry, autophagy, epithelial-mesenchymal transition (EMT), cancer cell stemness, temozolomide (TMZ) resistance, and NF-κB signaling. Downregulated DEGs were associated with TMZ resistance, glioma proliferation, RNA processing, and Wnt/β-catenin signaling. Key enrichment pathways, including NF-κB, Want, and BMP, are all critical for maintaining glioma stemness. FOSL1 was found to regulate RNA processing and ubiquitination. Notably, 8 upregulated (ITGA5, SDC1, PHLDB2, TNFRSF8, ADAM8, TLR7, STEAP3, and POU3F2) and 4 downregulated (IFIT1, FBXO16, ARL3, and BEX1) genes were identified, with implications for glioblastoma prognosis.Conclusion: This transcriptome investigation emphasizes the diverse functions of FOSL1 in different biological processes and signaling networks during the shift from proneural to mesenchymal state in glioblastoma.Keywords: glioma, RNA sequencing, FOSL1, NF-κB, glioma stem cells, signaling pathways